Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1084/jem.20050122
|View full text |Cite
|
Sign up to set email alerts
|

Divergent and convergent evolution after a common-source outbreak of hepatitis C virus

Abstract: The genomic sequences of viruses that are highly mutable and cause chronic infection tend to diverge over time. We report that these changes represent both immune-driven selection and, in the absence of immune pressure, reversion toward an ancestral consensus. Sequence changes in hepatitis C virus (HCV) structural and nonstructural genes were studied in a cohort of women accidentally infected with HCV in a rare common-source outbreak. We compared sequences present in serum obtained 18–22 yr after infection to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
191
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(206 citation statements)
references
References 27 publications
12
191
1
2
Order By: Relevance
“…HCV genotype was probably not a factor in the outcome of PD-1 blockade. The quality of T-cell immunity varies widely in humans and chimpanzees even when infection is established with viruses of the same genotype or subtype (7,13,14,(24)(25)(26)(27)(28)(29). It is therefore likely that successful PD-1 therapy in Ch5300 was due to priming and/or maintenance of a broad T-cell response that could be rescued regardless of HCV genotype.…”
Section: Resultsmentioning
confidence: 99%
“…HCV genotype was probably not a factor in the outcome of PD-1 blockade. The quality of T-cell immunity varies widely in humans and chimpanzees even when infection is established with viruses of the same genotype or subtype (7,13,14,(24)(25)(26)(27)(28)(29). It is therefore likely that successful PD-1 therapy in Ch5300 was due to priming and/or maintenance of a broad T-cell response that could be rescued regardless of HCV genotype.…”
Section: Resultsmentioning
confidence: 99%
“…22 For example, Timm et al 73 recently observed a strong association between sequence variation within an immunodominant HLA-B*8 restricted NS3 epitope and expression of HLA-B*8, also supporting reproducible allele-specific selection pressures at the population level. Ray et al 74 performed a study in the well-documented Irish cohort and compared sequences present in serum obtained 18-22 years after infection to sequences present in the shared inoculum. Of note, they observed that amino-acid substitutions in known epitopes were directed away from consensus in women expressing the restricting HLA allele (suggesting immune selection) and towards consensus in those lacking the allele (suggesting reversion).…”
Section: Role Of Class I Alleles In Hcv Infectionmentioning
confidence: 99%
“…[6][7][8] Mechanisms contributing to this progressive functional defect remain unclear but could involve (1) lack of CD4 T cell help, 7,9 (2) defective antigen-presenting cell function, 10 (3) impairment of HCV-specific immunity by regulatory T cells, 11 (4) expression of inhibitory receptors, 12,13 or (5) T cell exhaustion caused by chronic antigenic stimulation. The overall weak T cell responses observed along with viral persistence could also result from "holes" in the HCV-specific T cell repertoire or a preexisting functional defect of HCV-specific T cells before infection.…”
mentioning
confidence: 99%
“…Mutations of several HCV epitopes, described both in chimpanzees and humans, can lead to decreased viral recognition by CD8 T cells. [2][3][4][5] Functional decline of HCV-reactive T cells resulting from progressive loss of interleukin-2 (IL-2) …”
mentioning
confidence: 99%